Census Racial Metadata: Categories Used for Different Racial Groups Across Countries and Time. Issue 1 (14th October 2022) - Cheng, Siyao; Twidale, Michael
ABSTRACT: A national census enables a government to comprehend its population. Questions concerning race and ethnicity are often included in census forms. We examined the racial category options provided in 35 countries' historical census forms over multiple decadal censuses. Analysis of these metadata options can help in understanding the way that official measures of race are socially constructed and reconstructed over place and time according to changing circumstances.